Hepatocyte necrosis induced by oxidative stress and IL-1α release mediate carcinogen-induced compensatory proliferation and liver tumorigenesis - Sakurai, Toshiharu (2008)
Hepatocyte IκB kinase β (IKKβ) inhibits hepatocarcinogenesis by suppressing accumulation of reactive oxygen species (ROS) and liver damage, whereas JNK1 activation promotes ROS accumulation, liver damage and carcinogenesis. We examined whether hepatocyte p38α, found to inhibit liver carcinogenesis, acts similarly to IKKβ in control of ROS metabolism and cell death. Hepatocyte-specific p38α ablation enhanced ROS accumulation and liver damage, which were prevented upon administration of an antioxidant. In addition to elevated ROS accumulation, hepatocyte death, augmented by loss of either IKKβ or p38α, was associated with release of IL-1α. Inhibition of IL-1α action or ablation of its receptor inhibited carcinogen-induced compensatory proliferation and liver tumorigenesis. IL-1α release by necrotic hepatocytes is therefore an important mediator of liver tumorigenesis.